Blood-derived ratio indexes associated with severity and prognosis of immune checkpoint inhibitor-related cardiotoxicity: a retrospective analysis - Guo, Ling; Li, Zhenli; Gao, Guangbin; Liu, Jing; Guan, Zhengkun; Yao, Tiezhu; Liu, Guang; Jiao, Qian; Wang, Tenghui; Wang, Yansong; Ma, Jingtao (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have transformed cancer therapy but may cause immune checkpoint inhibitor-related cardiotoxicities (iRCs). Blood-derived inflammatory ratios may serve as practical prognostic tools for these life-threatening complications.MethodsWe conducted a retrospective study of 105 iRC patients treated with ICIs between 2020 and 2023. Patients were classified by Common Terminology Criteria for Adverse Events (CTCAE) severity grades. We identified the most important blood-derived ratio indexes at iRC diagnosis associated with the severity of iRCs, 40-day major adverse cardiovascular events (MACEs), and long-term mortality using receiver operating characteristic (ROC) analyses and restricted cubic spline (RCS) curves. Kaplan–Meier survival curves, Cox regression, and subgroup analysis were also performed to evaluate them.ResultsHigh-grade iRCs patients (n=40) showed a significantly higher system inflammation response index (SIRI) (8.21 vs. 2.21, p<0.001) and neutrophil-to-lymphocyte ratio (NLR) (11.46 vs. 5.81, p=0.001) than low-grade cases. SIRI >3.07 was strongly associated with 40-day MACEs [hazard ratios (HR)=6.56, p<0.001], whereas NLR >7.88 was associated with increased long-term mortality risk (HR = 2.33, p=0.003). Both SIRI and NLR remained significant after adjusting for cardiac biomarkers and clinical variables and were found associated with iRC severity-related cardiac biomarkers.ConclusionSIRI and NLR are effectively associated with iRC severity and could stratify the risk of developing poor short- and long-term prognoses. These readily available inflammatory indexes could improve risk assessment and guide clinical decision-making for iRC patients. However, further prospective studies should validate their utility in diverse populations.